Density, design and their impact on urban fabric - Sivam, Alpana; Karuppannan, Sadasivam (2008)
Urban consolidation has become one of the prime objectives of metropolitan planning across the world. It is based on the desire to increase population densities within existing built-up areas in cities through relaxation of regulations controlling building heights and bulk. There is a need to evaluate density and design and its impact on urban fabric to create good and feasible development. It is often assumed that high densities are inherently evil and that low densities are good. It is quite likely that living conditions in high-density residential developments is better than in the low-density areas. In the older areas of cities in many countries, despite high densities, living environment is often quite good. However, effects of high density could be negative that can give rise to unpleasant interferences but it can also be very positive leading to social cohesion. Planning can influence urban development through layout of services and other practices followed in design and subdivision. The economy in the planning of housing development considerably depends on judicious choices of these variables. High densities bring down total cost as well as cost of land per unit. However, design parameters such plot coverage, height, proportion of area under roads, open spaces etc also affect cost and the environment of residential development, over and above the density effects. This study discusses mutual relationships of density and design and their impact on urban fabric. It provides some guidelines for the planning of residential areas. It attempts to identify the relationships between density and design as well as density, design and urban fabric. No attempt has been made to suggest specific standards for density or other aspects of design.